Synthesis of palladium nanoparticles stabilized on Schiff base-modified ZnO particles as a nanoscale catalyst for the phosphine-free Heck coupling reaction and 4-nitrophenol reduction - Nuray Yılmaz Baran; Talat Baran; Mahmoud Nasrollahzadeh (Scientific Reports, 2023)
Abstract Recently, the development of heterogeneous nanocatalytic systems using solid supports has been gaining importance due to some advantages such as easy handling, high thermal stability, high efficiency, reusability, and so on. Therefore, the design of catalyst supports for the preparation of stable heterogeneous catalytic systems is of great importance. In this work, Schiff base-modified ZnO particles have been developed (ZnO–Scb) as a novel support. A heterogeneous nanocatalyst system has then been prepared by immobilizing palladium nanoparticles (Pd NPs) on the ZnO-Scb surface as the support. The resulting palladium nanocatalyst (Pd–ZnO–Scb) structure has been characterized by different analytical techniques (FT-IR, XRD, TEM, FE-SEM, elemental mapping and EDS) and used to catalyze the Heck coupling reactions and 4-nitrophenol (4-NP) reduction. Test results revealed that Pd–ZnO–Scb could effectively couple various aryl halides with styrene in yields of up to 98% in short reaction times. Pd–ZnO–Scb was also efficiently used in the complete 4-NP reduction within 135 s at room temperature. Additionally, it was found that Pd–ZnO–Scb was more effective than other reported catalysts in the Heck coupling reaction. Moreover, the recycling tests indicated that Pd–ZnO–Scb could be easily isolated from the reaction medium and reused in seven consecutive catalytic runs while retaining its nanostructure.